2015
DOI: 10.5194/amt-8-5009-2015
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison of snowfall estimates derived from the CloudSat Cloud Profiling Radar and the ground-based weather radar network over Sweden

Abstract: Abstract. Accurate snowfall estimates are important for both weather and climate applications. Ground-based weather radars and space-based satellite sensors are often used as viable alternatives to rain gauges to estimate precipitation in this context. In particular, the Cloud Profiling Radar (CPR) on board CloudSat is proving to be a useful tool to map snowfall globally, in part due to its high sensitivity to light precipitation and its ability to provide near-global vertical structure. CloudSat snowfall esti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 30 publications
0
51
0
Order By: Relevance
“…Both Cao et al () and Chen et al () show that NEXRAD‐based blended QPE datasets might be optimal for high snowfall rates compared to the 2CSP product (due to possible CPR attenuation effects), but CloudSat is conversely superior at detecting lighter snowfall events. Norin, Devasthale, L'Ecuyer, Wood, and Smalley () compare 2CSP with ground‐based scanning radar data in Sweden and show excellent snowfall rate distribution agreement between 0.1 and 1.0 mm/hr snowfall rates, also indicating good agreement between the two datasets when CloudSat overpasses are between 46 and 82 km from the radar sites, with degrading correlations at further distances. Possible CloudSat underestimation is also highlighted at the highest snowfall rates.…”
Section: Methodsmentioning
confidence: 97%
“…Both Cao et al () and Chen et al () show that NEXRAD‐based blended QPE datasets might be optimal for high snowfall rates compared to the 2CSP product (due to possible CPR attenuation effects), but CloudSat is conversely superior at detecting lighter snowfall events. Norin, Devasthale, L'Ecuyer, Wood, and Smalley () compare 2CSP with ground‐based scanning radar data in Sweden and show excellent snowfall rate distribution agreement between 0.1 and 1.0 mm/hr snowfall rates, also indicating good agreement between the two datasets when CloudSat overpasses are between 46 and 82 km from the radar sites, with degrading correlations at further distances. Possible CloudSat underestimation is also highlighted at the highest snowfall rates.…”
Section: Methodsmentioning
confidence: 97%
“…They found that the mean vertical profile of IWC is overestimated below 10-km heights, with peak values off by a factor of 2. In a second evaluation, Norin et al (2015) quantitatively intercompared snowfall estimates from a ground-based polarized C-band Doppler radar in Sweden to CloudSat estimates when the satellite passed overhead in the vicinity of the radar. Taking only those comparison cases where the radar and CloudSat measurements were relatively collocated (;30 km), they concluded that the 2C-SP retrieval algorithm (Wood et al 2013) has limited ability to retrieve at the higher end of the snowfall intensity distribution (.1mmh 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on Figure 1, Q snow appears to be the dominant cooling influence in the ocean during the top 20th percentile of snowfall events. Considering that CloudSat has noted limitations in retrieving snowfall rates above 1 mm/hr when compared with surface radar (Norin et al, 2015), it is likely that heavier snowfall rates which could lead to the most powerful cooling fluxes are undercounted. Further considering that calculations of Q snow are based on an uncertain assumption that the satellite retrieved rate of snowfall will equal the rate of snowmelt, the exact threshold when melting snow could become the dominant cooling flux is not confident.…”
Section: Resultsmentioning
confidence: 99%